Archival document focused on cultural production: the NOBRADE in the representation of the organic information about the theater costumes used in the play “Amor Barato” performed at the Teatro Castro Alves - Conceição, Alexandre da Silva; Barros, Susane Santos; Cunha, Francisco José Aragão Pedroza (Informação em Pauta, 2020)
The purpose of this communication is to contextualize the collection of costumes as archival documents. The costumes are produced and used in a staging to attend a cultural production and record elements of organic information, such as time, place, color, lifestyle, among others, reproducing the context of the activities that generated them. It is the result of a research of an applied nature, with a qualitative approach, through a systematic observation in the collection of the costumes of the Castro Alves Theater in Salvador, Bahia, Brazil. In relation to the objectives it is exploratory and descriptive, it uses a bibliographical and documentary revision to base the analyzes. The costumes have administrative, proof and memory values ​​of a collective entity. The results show that in the context of the creation of costumes is the link of information to the principles of provenience and organicity due to the function of the collective body. It is recommended that these collections receive archival treatment through the areas and elements of NOBRADE for the effectiveness of access to information recorded from the clothing created, received and accumulated by collective entities of cultural production.